Bibliometric Analysis of Digital Transformation in Business Strategic - Judijanto, Loso; Oktawiranti, Anggi; Za, Saida Zainurossalamia; Mahmuddin, Mahmuddin; Antoni, Antoni (West Science Business and Management, 2024)
This study employs a bibliometric analysis to explore the academic landscape of digital transformation in business strategy. Utilizing the Scopus database and VOSviewer software, the study analyzes key themes, research trends, and collaboration patterns from 2000 to 2023. The findings highlight the centrality of digital transformation in shaping organizational strategies and its strong connections with concepts such as digital business strategy, data analytics, and sustainability. Emerging trends include the growing integration of digital transformation with sustainable development goals and its application in specific industries such as manufacturing and SMEs. The study identifies prominent contributors and geographic hubs, revealing the dominance of developed countries in this field while noting limited representation from developing economies. Key challenges, such as data integration, conceptual ambiguity, and regional disparities, are discussed alongside opportunities for future research. This study provides valuable insights for academics, practitioners, and policymakers aiming to leverage digital transformation for strategic and sustainable business growth.